An investigation into Winterbach's approach to self-translation in Die boek van toeval en toeverlaat / The book of happenstance - Hofsajer, Anelda Susan (My University, 2011)
The aim is to determine the translation procedures and strategies adopted in the self-translation of Ingrid Winterbach’s Die boek van toeval en toeverlaat (2006)/The Book of Happenstance (2008). These procedures and strategies are compared to the strategies followed by two other South African self-translators, Dalene Matthee and André Brink. Vinay and Darbelnet’s translation procedures and strategies and Venuti’s notion of “invisibility” are used to analyse the author’s translation approach. To facilitate comparison with the translation strategies of Matthee and Brink, Vinay and Darbelnet are supplemented by a number of other translation strategies, such as rationalisation, explicitation and removal of foreshadowing. This study contributes to the study of literary translation in South Africa, specifically in the area of self-translation by a South African author for a South African audience.